Quality of Science Learning Services in The Covid-19 Pandemic - Andrias Andrias; Darnawati Darnawati; La Tarifu (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of online science learning at SMPN 3 South Wangi-Wangi did not work as it should. This study aims to determine the quality of learning services provided by teachers during the Covid-19 pandemic in terms of student satisfaction levels. The research method used in this study is a survey method with a quantitative approach. Data collection techniques in this study using questionnaires and documentation. The data analysis technique used in this study used descriptive statistical analysis. Based on the results of the study, it is known that the five indicators/dimensions of science learning services are considered to have met student expectations, with the assurance dimension obtaining the highest satisfaction score of 79.6% and the tangible dimension obtaining the lowest satisfaction score of 68%. So that after the overall calculation, it is known that the level of student satisfaction with science learning services during the Covid-19 pandemic is 73.13% so it can be categorized as satisfied. Thus, it can be concluded that the quality of science learning services at SMPN 3 South Wangi-Wangi during the Covid-19 pandemic was in a good category.